Human Rights in Indonesian Constitutional Amendements - Ahmad Tholabi Kharlie (Jurnal Cita Hukum, 2013)
Human Rights in Indonesian Constitutional Amendments. Indonesian constitutional amendments incorporated human rights principles into the Constitution of the Republic of Indonesia 1945 (UUD NRI), especially in the second amendment in 2000. Under that amendment, the UUD NRI currently stipulates human rights principles as provided for in the Universal Declaration of Human Rights (UDHR). However, there are some important notes, which at its core is a lack of emphasis on the vision and mission of the State in implementing human rights in Indonesia, as well as the existence of gaps between the norms of the Constitution and the Universal Declaration of Human Rights. DOI: 10.15408/jch.v1i1.2987